A New Breviane Spiroditerpenoid from the Marine-Derived Fungus Penicillium sp. TJ403-1 - Beiye Yang; Weiguang Sun; Jianping Wang; Shuang Lin; Xiao-Nian Li; Hucheng Zhu; Zengwei Luo; Yongbo Xue; Zhengxi Hu; Yonghui Zhang (Marine Drugs, 2018)
Marine-derived fungi are a promising and untapped reservoir for discovering structurally interesting and pharmacologically active natural products. In our efforts to identify novel bioactive compounds from marine-derived fungi, four breviane spiroditerpenoids, including a new compound, brevione O (1), and three known compounds breviones I (2), J (3), and H (4), together with a known diketopiperazine alkaloid brevicompanine G (5), were isolated and identified from an ethyl acetate extract of the fermented rice substrate of the coral-derived fungus Penicillium sp. TJ403-1. The absolute structure of 1 was elucidated by HRESIMS, one- and two-dimensional NMR spectroscopic data, and a comparison of its electronic circular dichroism (ECD) spectrum with the literature. Moreover, we confirmed the absolute configuration of 5 by single-crystal X-ray crystallography. All the isolated compounds were evaluated for isocitrate dehydrogenase 1 (IDH1) inhibitory activity and cytotoxicity, and compound 2 showed significant inhibitory activities against HL-60, A-549, and HEP3B tumor cell lines with IC50 values of 4.92 ± 0.65, 8.60 ± 1.36, and 5.50 ± 0.67 µM, respectively.